2018
DOI: 10.1111/jcmm.14036
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PRMT5/Akt signalling axis prevents human lung cancer cell growth

Abstract: The emerging evidence reveals that protein arginine methyltransferase 5 (PRMT5) is involved in regulation of tumour cell proliferation and cancer development. Nevertheless, the exact role of PRMT5 in human lung cancer cell proliferation and the underlying molecular mechanism remains largely obscure. Here, we showed that PRMT5 was highly expressed in human lung cancer cells and lung cancer tissues. Furthermore, we generated PRMT5 stable knockdown cell lines (A549 and H1299 cells) and explored the functions of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 20 publications
0
55
0
Order By: Relevance
“…Hence, this data highly suggest PRMT5 to be an upstream regulator of AKT signaling. Recently, PRMT5 has been reported to directly colocalize and interact with AKT in lung cancer cells, but it did not influence PTEN or mTOR (48).…”
Section: Discussionmentioning
confidence: 93%
“…Hence, this data highly suggest PRMT5 to be an upstream regulator of AKT signaling. Recently, PRMT5 has been reported to directly colocalize and interact with AKT in lung cancer cells, but it did not influence PTEN or mTOR (48).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown that Akt, also named PKB, was involved in cancer cell growth and tumor progression. Recently, several studies reported that PRMT5 interacted and regulated Akt activation in mouse liver cells 2 , lung cancer cells 7 , and lymphoma cells 13 . Nevertheless, it is still unclear whether PRMT5 promotes lung cancer cell death and chemosensitivity via regulation of Akt activity upon resveratrol treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that PRMT5 interacted with Akt and regulated Akt activation, which controlled cancer cell replication and growth 7 . Moreover, Akt is activated by PRMT5 through hyperphosphorylation of PI3-K and hypophosphorylation of PTEN 12 and co-localization of Akt 7 . These investigations mainly focused on the relationship between PRMT5 and Akt and related mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in lung cancer cells, PRMT5 was proved to promote cell proliferation through direct interaction with Akt and regulation of Akt activity. 21 More recently, PRMT5 was demonstrated that lead to FBW7 expression to promote tumorigenesis in pancreatic cancer. 14 ling, 24 and EGF-induced nuclear translocation of SHCBP1 directly increased acetylation of β-catenin to enhanced NSCLC cellular stemness, 25 which is suggested that EGFR signalling can drive β-catenin activation via various routes.…”
Section: Discussionmentioning
confidence: 99%